2006
DOI: 10.1002/jbm.b.30511
|View full text |Cite
|
Sign up to set email alerts
|

Transverse fracture of brittle bilayers: Relevance to failure of all‐ceramic dental crowns

Abstract: This study examines the behavior of cracks approaching interfaces in all-ceramic dental crown-like bilayers. Flat specimens are fabricated by fusing porcelain veneers onto yttria-tetragonal-zirconia-polycrystal (Y-TZP) and alumina core ceramic plates, with veneer/core matching to minimize residual thermal expansion mismatch stresses. Vickers indentations are placed on either side of the interfaces, at systematically decreasing distances, so that the lead corner cracks approach and intersect the interfaces in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 31 publications
1
42
2
Order By: Relevance
“…Arrested cone cracks also delaminate after extended cycling, into an annular configuration beyond the cone base [38]. By contrast, veneer cones never penetrate into the stiff, tough ceramic underlayer, even in specimens with abraded core top surfaces [15]. These subsidiary modes, while not in themselves responsible for primary failure, can nevertheless accelerate the catastrophic demise of crown-like layer structures.…”
Section: Crack Morphology and Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Arrested cone cracks also delaminate after extended cycling, into an annular configuration beyond the cone base [38]. By contrast, veneer cones never penetrate into the stiff, tough ceramic underlayer, even in specimens with abraded core top surfaces [15]. These subsidiary modes, while not in themselves responsible for primary failure, can nevertheless accelerate the catastrophic demise of crown-like layer structures.…”
Section: Crack Morphology and Failurementioning
confidence: 99%
“…Considerable recent work has been done on the way brittle layer structures consisting of a weak and relatively compliant "veneer" joined to a strong and stiff "core" and glued to a polymeric base fail in contact loading with spheres [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Such configurations are representative of occlusal loading of all-ceramic veneer/core dental crowns fixed to tooth dentin [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a strong thermal mismatch in a bilayered sample with the veneering layer having a thermal expansion coefficient of 5 μm/m・K led to tensile stress in the underlying zirconia. This stress was revealed by a Vickers indentation in the zirconia layer close to the interface, leading to strong crack propagation into the zirconia 12) . Stress in the veneering ceramic may develop only below the glass transition temperature (Tg).…”
Section: Introductionmentioning
confidence: 98%
“…Kim et al 22) evaluated radial cracks initiating from four corners of Vickers indentations imprinted in ceramic/ceramic bilayers. The radial cracks were affected by the elastic mismatch between the contacting ceramics, and the crack perpendicular to the interface was found to be the most sensitive to mismatch among the four cracks.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of crack slanting was greater for smaller marginal angles and shorter distances from the ceramic/resin interface. Several studies have reported on crack slanting or deflection in ceramic materials with a marginal angle of 90° 13,14,[22][23][24] . Crack slanting or deflection occurred with marginal angles of 45 and 60°.…”
Section: Discussionmentioning
confidence: 99%